Association of Different Forms of Child Maltreatment With Peer Victimization in Mexican Children and Adolescents - Martín-Babarro, Javier; Toldos, M. Paz; Paredes-Becerra, Lorena; Abregu-Crespo, Renzo; Fernández-Sánchez, Juan; Díaz-Caneja, Covadonga M. (Frontiers in Psychology, 2021)
Objective: This study aims to examine the relationship between exposure to multiple forms of child abuse and neglect within the family context and peer victimization at school, accounting for the moderator effect of sex and educational level. Methods: 2,415 children and adolescents, aged 9 to 15 years, attending public schools in Mexico completed the Childhood Trauma Questionnaire-Short Form and a modified version of the Olweus’ Bully/Victim Questionnaire. Linear regression models were used to assess the association of five different forms of child abuse or negligence (emotional, physical and sexual abuse, and emotional and physical negligence) with three forms of peer victimization (direct, indirect and cyberbullying). Results: Direct forms of child abuse within the family (i.e. emotional, physical and sexual abuse), but not neglect, were significantly associated with an increased risk for peer victimization. In the fully adjusted models, emotional abuse was significantly associated with the three types of bullying victimization [indirect b = .48, t = 6.75, p < .001, direct (b = .47, t = 4.89, p < .001), and cyberbullying (b = .85, t = 5.45, p <. 001)], while physical abuse was significantly associated with increased indirect (b = .17, t = 2.43, p < .01) and direct victimization (b = .29, t = 3.28, p < .01), but not with cyberbullying. Boys suffering sexual abuse within the family context showed higher levels of all subtypes of peer victimization. Students attending secondary school who suffered sexual abuse showed higher levels of indirect victimization than students attending primary schools. Conclusion: Child abuse within the family context seems to increase the risk for peer victimization. Preventive strategies to address bullying and promote resilience should take into account family factors. Interventions for high-risk families might be useful to prevent child multivictimization.